2021
DOI: 10.1128/jvi.00460-21
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinating Enzyme USP21 Inhibits HIV-1 Replication by Downregulating Tat Expression

Abstract: Ubiquitination plays an important role in human immunodeficiency virus-1 (HIV-1) infection. HIV proteins such as Vif and Vpx mediate the degradation of the host proteins APOBEC3 and SAMHD1, respectively, through the proteasome pathway. However, whether deubiquitylating enzymes play an essential role in HIV-1 infection is largely unknown. Here, we demonstrate that the deubiquitinase, USP21, potently inhibits HIV-1 production by indirectly downregulating the expression of HIV-1 trans-activator of transcription (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…USP29-HA C294A was generated from USP29-HA using site-directed mutagenesis. Ub-Flag/Myc ( 10 ), RIG-I(N)-Myc ( 26 ), MAVS, IFN-β-Luc, NF-κB-Luc, and Renilla ( 27 ) have been previously described. The SARS-CoV-2 GFP/ΔN (Wuhan-Hu-1, MN908947, Clade:19A) expression plasmid was constructed by replacing the regions encoding viral N (from nucleotide positions 28274 to 29533) based on the MN908947 genome with the GFP reporter gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…USP29-HA C294A was generated from USP29-HA using site-directed mutagenesis. Ub-Flag/Myc ( 10 ), RIG-I(N)-Myc ( 26 ), MAVS, IFN-β-Luc, NF-κB-Luc, and Renilla ( 27 ) have been previously described. The SARS-CoV-2 GFP/ΔN (Wuhan-Hu-1, MN908947, Clade:19A) expression plasmid was constructed by replacing the regions encoding viral N (from nucleotide positions 28274 to 29533) based on the MN908947 genome with the GFP reporter gene.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-1 is a well-studied pathogen that manipulates the host's ubiquitin network to antagonize host restriction factors ( 5 9 ). In contrast, the host also utilizes the ubiquitin-proteasome system (UPS) to destabilize viral proteins such as deubiquitination by the deubiquitinating enzyme (DUB) USP21 of the HIV-1 protein Tat, which leads to Tat instability ( 10 ). Recent reports have shown that the E3 ubiquitin ligases RNF5 and CRL2 (ZYG11B) are recruited by membrane protein and ORF10 protein of SARS-CoV-2, respectively; However, CRL2 is dispensable for SARS-CoV-2 infection ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although two studies found that USP21 maintained the protein level of EZH2, the enzymatic catalytic subunit of the polycomb repressive complex 2 that can modulate gene expression by trimethylating K27 on histone 3 (H3K27), in which the impacts of USP21 on H3K27me3 level were not tested ( Chen et al, 2017b ; Ma et al, 2021 ). Reciprocally, USP21 expression dramatically elevated H3K9 methylation without affecting H3K4 methylation or H3K27 acetylation on the promoter of cyclin T1, which resulted in decreased cyclin T1 expression ( Gao et al, 2021 ). Whether this correlates with the hydrolysis of H2Aub remaines unclear.…”
Section: Role Of Usp21 In Diverse Biological Processesmentioning
confidence: 99%
“…The recent identification of USP21 as the DUB responsible for the stabilization of AIM2 and immediate AIM2 inflammasome activation upon DNA stimulation further complicates the role of USP21 in regulating DNA-mediated innate immunity ( Hong et al, 2021 ). Moreover, another study indicated that USP21 inhibits human immunodeficiency virus 1 (HIV-1) replication in vitro by downregulating the expression of transactivator of transcription (Tat), which is essential for transcriptional elongation in HIV-1 ( Gao et al, 2021 ). Collectively, these studies suggested a dual role for USP21 in anti-viral infections.…”
Section: Role Of Usp21 In Diverse Biological Processesmentioning
confidence: 99%
“…[35][36][37][38][39][40] HIV-1 is a well-studied pathogen, [41,42] and our studies and those of other groups have discovered several different modes of DUB regulation of HIV-1 replication by targeting either virus or host proteins. [43][44][45][46][47][48] For example, some DUBs have different effects on HIV-1 infectivity by targeting the HIV-1 Tat protein. Ubiquitin-specific protease 7 (USP7) promotes HIV-1 production by stabilizing Tat protein, [49] whereas our recent study showed that USP21 inhibits HIV-1 replication by downregulating Tat expression.…”
Section: Introductionmentioning
confidence: 99%